Perspectives on the world income distribution: beyond twin peaks towards welfare conclusions - Hajo Holzmann; Sebastian Vollmer; Julian Weisbrod (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
This paper contributes towards the growing debate concerning the world distribution of in- come and its evolution over that past three to four decades. Our methodological approach is twofold. First, we formally test for the number of modes in a cross-sectional analysis where each country is represented by one observation. We contribute to existing studies with technical improvements of the testing procedure, enabling us to draw new conclusions, and an extension of the time horizon being analyzed. Second, we estimate a global distribution of income from national log-normal distributions of income, as well as a global distribu- tion of log-income as a mixture of national normal distributions of log-income. From this distribution we obtain measures for global inequality and poverty as well as global growth incidence curves.
Keywords: O0; C5; I3; F0; 330; Einkommensverteilung; Armut; Entwicklungskonvergenz; Wirtschaftswachstum; Welt